Association of Household Environment and Family Habits with Respiratory Allergy Symptoms in Children - Lilis Sulistyorini; Corie Prasasti; Ririh Yudhastuti; Hasnur Z Arna (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: Respiratory allergy symptoms in children still pose challenges in Indonesia regions, including big cities such as Surabaya. Several studies have found a relationship between household environment and family habits. The study aimed to identify the relationship between household environment and family habits with the incidence of respiratory allergies in children. Methods: This study used a cross-sectional design and was conducted on children aged 5-15 years with respiratory problems in the past three months. A questionnaire adapted from the International Childhood Asthma and Allergy Research (ISAAC) was used to see the respiratory allergy symptoms occurring in children. For statistical tests, this study used the Chi-square test, Fisher exact test, and logistic regression. Results : The data obtained showed a significant relationship between home furniture and building condition with respiratory allergy symptoms in children with OR values of 3.667 (CI: 1.068-12.586) and 3.747 (CI: 1.149-12.221), respectively. The use of air fresheners and insect repellent at home was also significantly related to respiratory allergy symptoms in children with OR values of 3.286 (CI: 1.063-10.152) and 4.200 (CI: 1.270-13.892), respectively. Conclusion: Household environment and family habits are associated with respiratory allergy symptoms in children. Household environment and family habits should be considered carefully, especially home furniture and building condition, also the habits of using fresheners and insect repellent should be avoided to prevent respiratory allergy symptoms in children. Conducting similar research and examination that involve larger samples to explore the cause-and-effect relationship between household environment and family habits with respiratory disease are very needed